Firm level attributes of sustainability disclosure compliance: moderating role of institutional quality - Bello, Mohammed Sabo; Mohd Said, Ridzwana; Nazir Gardazi, Syeda Saba (Sciencedomain International, 2024)
Corporate Sustainability Disclosure Compliance (CSDC) has become increasingly important globally as stakeholders demand greater transparency and accountability from companies regarding their environmental, social and governance (ESG) practices. However, the extent to which companies comply with sustainability disclosure requirements can vary depending on the quality of the institutional environment in which they operate. In Nigeria, a country with a diverse economic landscape and varying levels of institutional quality, understanding how institutional factors influence firms' compliance with sustainability reporting guidelines is critical to promoting sustainable business practices and improving corporate governance standards. Therefore, the purpose of this study is to identify the factors influencing CSDC by examining the moderating effect of institutional quality using the rule of law as a proxy. Based on the theoretical framework of new institutionalism, a set of hypotheses was formulated and subsequently tested using a dataset of 118 listed companies from 2011 to 2017. The study found a statistically significant and positive relationship between the rule of law and CSDC in the Nigerian context. However, there was no statistically significant evidence to support the relationship between liquidity and the rule of law. In contrast, the relationship between industry type and the rule of law, as well as the relationship between leverage and the rule of law, were both positive and significant, suggesting better compliance with transparency in the presence of efficient legal systems. However, the interaction between taxation and the rule of law showed a negative relationship, highlighting the need for caution in interpreting its moderating role. This study contributes to existing knowledge, policy and practice by highlighting the moderating effect of the rule of law.